Effect of Heat Exposure Time on Tensile Properties in Cold Rolled Steel (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper presents the effect of heat exposure time on tensile strength of cold rolled specimens. Welding and process annealing are applied to the specimens to investigate their implications. The two processes involve heat and time but in differential amounts. In welding the temperature raises to levels far beyond the melting point of the specimens and cools quickly. The case is different in process anneal the specimen temperature increases slowly to the subcritical level and cools slowly after a specific soaking time. Welded and process annealed in the form of tensile specimens are tested in the tensile machine until fracture. The test results showed that welding and process annealing caused a decrease in yield strength by one third and almost two thirds respectively compared with the as rolled. The fracture of the welded specimen was localized at the heat affected zone near the weld line but was random in all other specimens. Percentage elongation was lowest in the welded specimen compared with other patches of specimens.